Evaluación del riesgo psicosocial y su incidencia en el desempeño laboral del docente de la unidad educativa ramón barba naranjo de la ciudad de Latacunga sección matutina en el año 2015. Propuesta de un programa de prevención de riesgos psicosociales. - Rodríguez Balarezo, Augusto Germánico (2016)
The following research has as purpose to evaluate the psychosocial risks to teachers of the Ramon Barba Naranjo Educative Unity in the Morning Section, in response to the continuing health problems that have been presented in teachers, and developing a program of prevention, to reduce the stress levels and other health problems presented in the staff of the institution. To carry out this research a Risk Matrix it has elaborate and implemented by the Ministry of Labour; then the Psychosocial Risk Factors questionaire was applied to the total teachers; where the reality was researched in which teachers carry out their daily of work, it took place a routinnary day, with a response rate was achieved to the reality investigated. With the results it was possible to know the critical points that there is in the institution, such as: communication, responsibility, mobbing, and group cohesion. The purpose of Risk Prevention Program is to prevent and reduce psychosomatic diseases; and promote wellness in the workplace, where preventive measures are established to control high-risk aspects. Thus it concludes that the risk factors will decrease at the moment to start the implementation of this support tool.